Royal Canopy over the Church Entrance: Forms, Spatial Contexts, Iconographic Programs, and Meaning of the Dome in Serbian Narthexes of the 14th Century - Stanković, Nebojša P. (Collection of Papers of the Faculty of Philosophy in Priština, 2024)
The churches commissioned by King (later Emperor) Stephen Dušan, his important dignitaries, and later Serbian rulers—e.g., Holy Archangels near Prizren, Lesnovo, Hilandar, Markov Manastir, Ravanica, and Manasija—often have a narthex or an entrance porch covered by a dome. This architectural element is additionally emphasized by a specific program of painted decoration—as witnessed by several preserved ensembles—which, like the one in the nave’s dome, contains some representation of Christ surrounded by members of the heavenly ranks. Through the choice of iconographic elements of Christ or accompanying personages, these compositions are often imbued with a royal subtext. Such an architectural and iconographic solution has its precedents in some Byzantine monuments from the 10th to the 12th century, of which the most important for the Serbian examples, as their potential models, are probably the Athonite katholika and the main church of the Pantokrator Monastery in Constantinople. The prevalence of this architectural element notably increased during the Late Byzantine period, particularly in political entities whose rulers sought independence and even aspired to imperial dignity, such as Epirus, which bordered the Serbian state, and later Mystra. In these Byzantine churches, the specific form of this micro-architectural feature and its strategic placement at the church entrance can be associated with imperial patronage and royal visits. Given the well-supported hypothesis that this paradigm was adopted into Serbian architecture with the same imperial connotation, this study examines its spatial, formal, and iconographic elements, along with its semantic and ideological context. The author’s ongoing research of this phenomenon encompasses all preserved and relevant examples within the Serbian Empire, Byzantium, and the broader Byzantine world. However, for the purpose of this article, the discussion will be limited only to Serbian monuments, include an examination of their potential models, and underscore particular nuances in meaning exhibited by their spatial solutions and iconographic programs.
Keywords: dome; canopy; narthex; Medieval Serbia; Emperor Stephen Dušan; royal aspects